-1-6d=1-5d-6

Simple and best practice solution for -1-6d=1-5d-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-6d=1-5d-6 equation:



-1-6d=1-5d-6
We move all terms to the left:
-1-6d-(1-5d-6)=0
We add all the numbers together, and all the variables
-6d-(-5d-5)-1=0
We get rid of parentheses
-6d+5d+5-1=0
We add all the numbers together, and all the variables
-1d+4=0
We move all terms containing d to the left, all other terms to the right
-d=-4
d=-4/-1
d=+4

See similar equations:

| .2x+x=300 | | 56/t=14 | | `2x+4-2=12` | | -3b-6=-2b-4 | | -10c-4-16c=-8(3c-1) | | (6x−14)+(4x−8)+(x+15)=180 | | -20+17b-20=3(9b+20) | | 4m+2m(m=9) | | x/2-12=32 | | 42/t=14 | | -7-19p=-8-19p+1 | | 113=5u+13 | | .47^2x=1/4 | | (x+20)3=5x | | -16-15z=-17z+18-15z | | -2u+5.52=4.22 | | 9u-9u=24 | | 16+7v-12=7v+4 | | Y=63x+825 | | x/49=30/35 | | 10-10h=10+12-10h | | 3x−7= 7x+13 | | 3+3v=12.9 | | −6=x5 | | Y+3+15+12=x-3 | | 3(x)+x+2(x)-1=251 | | -12=4f+8 | | 5y(y+2/5)=-13 | | 150-x-2x=120+2xX= | | 3y+4=2y+3 | | 6x−8=  8x | | 10w+2=10w+2=  8282 |

Equations solver categories